Living without free will - Pereboom, Derk, 1957- (Cambridge studies in philosophy., 2001)
Derk Pereboom argues that our best scientific theories have the consequence that factors beyond our control produce all of the actions we perform, and that because of this, we are not morally responsible for any of them. In addition, adopting this perspective would provide significant benefit for our lives.